EFFECT OF APPLICATIONS ON ELABORATION STRATEGIES FOR TEACHING STACCATO TECHNIQUE IN PIANO EDUCATION - Mehmet Kayhan KURTULDU (Fırat University, 2020)
In this study, staccato technique which is an important technical skill and taught to students during piano education process is discussed. In this context, practices related to teaching the technique with different simulations based on elaboration were made. In order to perform the applications, 4 groups were formed, which one is a control group. While classical study was conducted with the control group, it was ensured that elaboration strategies were applied with the help of different simulations with each of the experimental groups. Applications were made individually with each student during 40 minutes. In experimental applications, staccato technique was studied with first group woodpecker simulation, second group with ping-pong ball simulation, and third group with needle prick simulation. For the study, a piano piece which was suitable for the subject and technique was written by the researchers and used in the practices. Studies conducted with experimental and control groups, each consisting of 5 individuals, were evaluated with the scoring key developed by Kurtuldu (2010). The numerical data obtained from the groups were statistically processed and the results were analyzed with the help of comparative measurements. Normality hypothesis testing was used to determine the correct direction in comparative measurements. In this application, skewness and kurtosis coefficients were examined. Non-parametric measurements were preferred because the results did not meet the normal distribution assumption. According to the results obtained from the analysis, the experimental groups differed from the control group. It was observed that the second experimental group (ping-pong ball simulation) was more successful in applying the staccato technique among the experimental groups.